Rapid on-site visualization detection system for Fusarium oxysporum f. sp. cubense tropical race 4 utilizing RPA-CRISPR/Cas12a - Zhu, Lili (Plant disease, 2025)
Fusarium wilt of banana, a disease with devastating impacts on banana plants, is primarily caused by a pathogenic fungus called Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4). To facilitate control and interrupt the spread of Fusarium wilt of banana, we developed a rapid on-site visualization system for detecting Foc TR4 based on Recombinase polymerase amplification (RPA) combined with CRISPR/Cas12a. Based on Foc TR4-specific sequences, primers, crRNA, and ssDNAs were designed. The detection system exhibited high specificity, with amplification signals observed exclusively in samples containing Foc TR4. Additionally, the system showed high sensitivity, with a limit of detection (LOD) of approximately 20 copies and high efficiency, with detection results generated within 1 h from time of amplification. Notably, this method does not require large-scale instruments, making it a convenient and rapid approach. The detection system represents the first instance of on-site visualization of Foc TR4. This system can be employed for early detection of Foc TR4 and can provide a technical reference for the rapid detection and applications in the field of other pathogens